The Influence Of Time Budget Pressure And Locus Of Control On Audit Judgment Of The BPKP Aceh - Eva Susanti; Cut Fitrika Syawalina; Fathul Khaira (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this research is to determine the influence of time budget pressure, internal locus of control and external locus of control on audit judgment. This research is quantitative research and uses a questionnaire which is distributed to respondents. The selection of respondents was based on a purposive sampling technique on 58 auditors at the Aceh Financial and Development Supervisory Agency (BPKP) Representative office. The data analysis method used in this research is multiple linear regression analysis. The research results show that Simultaneously the time budget pressure, internal locus of control and external locus of control abilities influence the audit judgment. Furthermore the results of partial hypothesis testing show that the time budget pressure has a positive abilities influence on audit judgment, internal locus of control has a negative abilities influence on audit judgment, external locus of control has a positive abilities influence on audit judgment.